PENERAPAN METODE PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) DALAM MENINGKATKAN KETERAMPILAN PERMAINAN BOLA KASTI MATA PELAJARAN PENJASKES PADA SISWA KELAS V SD NEGERI 163099 TEBING TINGGI - Sabarina Br. Barus (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This purposes of this research is to improve learning result on physical education subject  through team games tournament (TGT) method. This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from grade V SD Negeri 163099 Tebing Tinggi which amounted to 32 students. The source of the data from observer, students and teacher. Data collection are by test and observation. This research used a qualitative descriptive analysis technique with percentage. The results showed that the use of TGT method at physical education can improve the ability of hitting and throwing in baseball which is characterized by increased mastery learning students, namely pre-cycle (59,37%), cycle I (81,25%), Cycle II (93,75%) and complete learn the clasical equal to 93,75 % in cycle II.Keywords: Hitting, Throwing, Baseball